Utilização da biointerface nanofios/enzimas para o desenvolvimento de biossensores nanoestruturados - Gerola, Gislaine Passarella [UNESP] (2014)
This project has as main objective the development of nanowires for application in biosensors. Nanomaterials have been highlighted by high sensitivity when applied to biological sensors. As they haver virtually the same dimensions as the molecules that should detect, these nanosensors could revolutionize the diagnoses way are made in medical and biological examinations. Therefores, in this research, we prepared and characterized multithreaded nanowires usind different types of metal and polymer. These nanowires were prepared by electrochemical deposition process and characterized by scanning electron microscopy (SEM). The synthesized nanowires have been changed for the attachment of the enzyme glucose oxidase. Several experimental parameters of biosensor was evaluated as the optimization of pH (at 6), as a function of the peak current obtained from glucose; the enzyme concentration of 0,4 mg ml-1 required to prepare the biosensor; as well as the study of electrochemical potential variation, where it was observed that the ideal is to use potential less than 0,4 V. The analyitcal curve for the determination of glucose showed a slope of 7.95 uA mol-1, with a correlation coefficient of 0.997 and detection limit of the biosensor determined was 3.7 x 10-7 mol L-1. The biosensor showed high selectivity only for detection of glucose and maintained a good response to glucose sensing (85%) in 30 days. Thus, the use of nanowires for the preparation of biosensors becomes and alternative to direct detection of glucose; the enzyme concentration of 0.4 mg ml-1 required to prepare the biosensor; as well as the study of electrochemical potential less than 0.4 V. The analytical curve for the determination o glucose showed a slope of 7.95 uA mol-1, with a correlation coefficient of 0.997 and detection limit of the biosensor...